Suitability analysis of new air quality monitoring stations in Krakow as related to assessment of spatial and temporal variability of PM10 concentrations - Gorzelnik, Tomasz; Oleniacz, Robert (Geomatics and Environmental Engineering, 2019)
The exceedance of air quality standards in urban agglomerations leads local communities to take actions that aim to improve aerosanitary conditions. For these actions to be efficient, it is essential to regularly collect accurate quantitative data that is able to characterize the degree of ambient air pollution. In order to achieve this objective, air quality monitoring systems are constantly being extended.In this paper, the usefulness of newly established air quality measuring stations in Krakow was examined. The assessment was carried out using statistical me-thods on the basis of the spatial and temporal variability of particulate matter (PM10) air concentrations over the period of 2016‑2017. In the analysis, meteorological data (wind directions) were applied. The main part of this assessment was a pairwise comparison of the PM10 concentrations measured at particular stations. The differences between the average values and the Pearson correlation coefficient were considered. In order to verify the statistical significance of the obtained results, the t-Student test was conducted. The greatest absolute differences between the measured values occurred during the autumn-winter period (heating season). Notwithstanding the foregoing, a high variability was also observed among the traffic stations.